Vous êtes sur la page 1sur 5

Formule de calcul prescurtat

2
1) (x + 2) = 2) (x – 1)2 = 3) (x + 3)2 = 4) (x – 4)2 =
5) (2x – 3)2 = 6) (2x + 1)2 = 7) (3x + 5)2 = 8) (2x – 7)2 =
9) (3x – 2)2 = 10) (4x – 1)2 = 11) (3x – 1)2 = 12) (2x + 5)2 =
13) (4x + 3)2 = 14) (x + 6)2 = 15) (6x – 5)2 = 16) (8x + 3)2 =
17) (10x + 3)2 = 18) (5x + 1)2 = 19) (7x – 2)2 = 20) (5x – 3)2 =
21) (2 – x)2 = 22) (5 – 2x)2 = 23) (5 – 8x)2 = 24) (9 – 2x)2 =
25) (11 – x)2 = 26) (6 – 4x)2 = 27) (3 – 7x)2 = 28) (2 – 9x)2 =
29) (5 – 7x)2 = 30) (1 – 12x)2 = 31) (1,3 – x)2 = 32) (1,8x + 1)2 =
33) (2x – 4,2)2 = 34) (3x – 1,6)2 = 35) (2,6 + 3x)2 = 36) (7,2 + 2x)2 =
37) (3,4 + x)2 = 38) (6,1 – 5x)2 = 39) (7x – 2,3)2 = 40) (6x – 4,5)2 =

41) x  2  
2

42) x  3  
2

43) x 2  3  
2
44)  
2x 1 
2

45)  3  2 x   46) 3  5 x   47)  6 x  1   


2 2 2 2
48) 2 3 x  1 
49)  2 x  7   50)  6 x  5  51) 3 2 x  5  52)  x 3  4
2 2 2 2

53)  2 2  x   54)  x  4 3   55)  2  6 x  


2
2 2 2 1 3
56)  x   
 3 2
2 2 2 2
4 1 7 3  5 1 3 1 
57)  x    58)   x   59)  x    60)   x  
5 8 2 4  3 4 7 3 
2 2 2 2
4 1 2 1  4 1  7 3 
61)  x    62)   x   63)  x    64)   x 
3 5 5 8  9 12   2 14 
2
6 7 
65)  x   
5 12 

Răspuns: 1) x2 + 4x + 4; 2) x2 – 2x + 1; 3) x2 + 6x + 9; 4) x2 – 8x + 16; 5) 4x2 – 12x


+ 9; 6) 4x2 + 4x + 1; 7) 9x2 + 30x + 25; 8) 4x 2 – 28x + 49; 9) 9x2 – 12x + 4; 10) 16x 2
– 8x + 1; 11) 9x2 – 6x + 1; 12) 4x2 + 20x + 25; 13) 16x2 + 24x + 9; 14) x2 + 12x + 36;
15) 36x2 – 60x +25; 16) 64x2 + 48x + 9; 17) 100x2 + 60x + 9; 18) 25x2 + 10x + 1; 19)
49x2 – 28x + 4; 20) 25x 2 – 30x + 9; 21) 4 – 4x + x 2; 22) 25 – 20x + 4x2; 23) 25 – 80x +
64x2; 24) 81 – 36x + 4x2; 25) 121 – 22x + x2; 26) 36 – 48x + 16x2; 27) 9 – 42x + 49x2;
28) 4 – 36x + 81x2; 29) 25 – 70x + 49x2; 30) 1 – 24x + 144x 2; 31) 1,69 – 2,6x + x2;
32) 3,24x2 – 3,6x + 1; 33) 4x2 – 16,8x + 17,64; 34) 9x2 – 9,6x + 2,56; 35) 6,76 + 15,6x
+ 9x2; 36) 51,84 + 28,8x + 4x2; 37) 11,56 + 6,8x + x2; 38) 37,21 – 61x + 25x2; 39) 49x2
– 32,2x + 5,29; 40) 36x2 + 54x + 20,25;
41) x 2  2 2 x  2; 42) x 2  2 3 x  3; 43) 2 x 2  6 2 x  9; 44) 2 x 2  2 2 x  1; 45) 3  2 6 x 
 2 x 2 ; 46) 9  6 5 x  5 x 2 ; 47) 6 x 2  2 6 x  1; 48) 12 x 2  4 3 x  1; 49) 4 x 2  4 7 x  7;
50) 6 x 2  10 6 x  25; 51) 18 x 2  30 2 x  25; 52) 3 x 2  8 3 x  16; 53) 8  4 2 x  x 2 ; 54)
1 2 9 16 2 1 1 49 21
x 2  8 3 x  48;55) 4  4 6 x  6 x 2 ; 56)
x  x  ; 57) x  x ; 58)  x
9 4 25 5 64 4 4
9 2 25 2 5 1 9 2 1 16 2 8 1 4 1 1
 x ; 59) x  x ; 60)  x  x 2 ; 61) x  x ; 62)  x ;
16 9 6 16 49 7 9 9 15 25 25 10 64
16 2 2 1 49 3 9 36 2 7 49
63) x  x ; 64)  x x 2 ; 65) x  x .
81 27 144 4 2 196 25 5 144
66) (x–2)·(x+2) = 67) (2x–1)·(2x+1) = 68) (8x–3)·(8x+3) =
69) (x+4)·(x–4) = 70) (3x+4)·(3x–4) = 71) (5x+2)·(5x–2) =
72) (4x–3)·(4x+3) = 73) (9x+4)·(9x–4) = 74) (10x+7)·(10x–7) =
75) (6x–5)·(6x+5) = 76) (12x+1)·(12x–1) = 77) (14x–3)·(14x+3) =
78) (7x–1)·(7x+1) = 79) (15x+8)·(15x–8) = 80) (13x–5)·(13x+5) =
81) (3x–2)·(3x+2) = 82) (4x–1)·(4x+1) = 83) (5–2x)·(5+2x) =
84) (6–5x)·(6+5x) = 85) (7–4x)·(7+4x) = 86) (4–9x)·(4+9x) =
87) (11x–3)·(11x+3) = 88) (16x+3)·(16x–3) = 89) (9–5x)·(9+5x) =
90) (8–7x)·(8+7x) = 91) (3–10x)·(3+10x) = 92) (7x–5)·(7x+5) =
93) (8x–7)·(8x+7) = 94) (20x–7)·(20x+7) = 95) (17x–3)·(17+3) =
96) (1,6–2,3x)·(1,6+2,3x) = 97) (4,3x+2,7)·(4,3x–2,7) = 98) (3,6+2,1x)·(3,6–2,1x) =
99) (4,5–3,2x)·(4,5+3,2x) = 100) (7,1–1,4x)·(7,1+1,4x) = 101) (6,3–4,2x)·(6,3+4,2x) =
102) (3,9x+4,7)·(3,9x–4,7) =103) (1,8x+3,8)·(1,8x–3,8) = 104) (2,7x+3,5)·(2,7x–3,5) =
 
105) 3 x  2  3 x  2  106) 3 2  x   3 2  x   107)  2 3  2 x    2 3  2 x  
108)  x  6    x  6   109)  2 x  5    2 x  5   110 )  2 3  x    2 3  x  
111)  3  2 2 x    3  2 2 x   112 )  13  6 x    13  6 x   113)  8  2 3 x    8  2 3 x  
114 )  5  2 x    5  2 x   115)  7 2  15 x    7 2  15 x   116 )  7  6 x    7  6 x  
117 )  11 x  7    11 x  7   118)  4 6  3 x    4 6  3 x   119 )  5  6 x    5  6 x  
2 1 2 1 3 2 3 2 7 5  7 5 
120)  x     x    121)  x     x    122)   x     x  
3 4 3 4 5 3 5 3 2 2  2 2 
 12 3   12 3  15 4   15 4  18 21   18 21 
123)  x   x   124)  x   x  125)  x  x 
 5 13   5 13   4 5   4 5   7 5   7 5 
 23 3   23 3   32 2   32 2   7 19   7 19 
126)  x   x   127)  x  x   128)   x  x 
 5 26   5 26   3 33   3 33   43 5   43 5 

Răspuns: 66) x2 – 4; 67) 4x2 – 1; 68) 64x2 – 9; 69) x2 – 16; 70) 9x2 – 16; 71) 25x2 – 4;
72) 16x2 – 9; 73) 81x2 – 16; 74) 100x2 – 49; 75) 36x2 – 25; 76) 144x2 – 1; 77) 196x2 – 9;
78) 49x2 – 1; 78) 225x2 – 64; 80) 169x2 – 25; 81) 9x2 – 4; 82) 16x2 – 1; 83) 25 – 4x2; 84)
36 – 25x2; 85) 49 – 16x2; 86) 16 – 81x2; 87) 121x2 – 9; 88) 256x2 – 9; 89) 81 – 25x2;
90) 64 – 49x2; 91) 9 – 100x2; 92) 49x2 – 25; 93) 64x2 – 49; 94) 400x2 – 49; 95) 289x2
– 9; 96) 2,56 – 5,29x2; 97) 18,49x2 – 7,29; 98) 12,96 – 4,41x2; 99) 20,25 – 10,24x2;
100) 50,41 – 1,96x2; 101) 39,69 – 17,64x2; 102) 15,21x2-22,09; 103) 3,24x2 – 14,44;
104) 7,29x2 – 12,25; 105) 9x2 – 2; 106) 18 – x2; 107) 12 – 2x2; 108) x2 – 6; 109) 4x2 – 5;
110) 12 – x2; 111) 3 – 8x2; 112) 13 – 6x2; 113) 8 – 12x2; 114) 5 – 2x2; 115) 98 – 15x2;
4 2 1
x 
116) 7 – 6x2; 117) 11x2 – 7; 118) 96 – 9x2; 119) 5 – 6x2; 120) ;
9 16
9 2 4 49 25 2 144 2 9 225 2 16 324 2 441
121) x  ;122)  x ;123) x  ;124) x  ;125) x  .
25 9 4 4 25 169 16 25 49 25

129) (x2 + 2x + 3)2 = 130) (2x2 – x – 1)2 = 131) (x2 – 3x – 1)2 =


132) (3x2 – 2x – 4)2 = 133) (x2 – x – 5)2 = 134) (x2 + 2x + 4)2 =
135) (3x2 – x – 4)2 = 136) (4x2 + 3x – 2)2 = 137) (2x2 – 5x + 1)2 =
138) (5x2 – x + 4)2 = 139) (x2 + 3x – 2)2 = 140) (2x2 – x + 5)2 =
141) (3x2 – 3x – 1)2 = 142) (6x2 – 2x – 3)2 = 143) (4x2 – 5x + 2)2 =
144) (0,5x2 + 1,2x + 2,4)2 = 145) (1,6x2 + 1,5x + 2,6)2 = 146) (3,4x2 – 2,6x + 1,5)2
=
147) (4,4x2 – 1,6x – 2,5)2 = 148) (2,8x2 – 3,2x + 3,5)2 = 149) (6,4x2 – 1,6x – 4,5)2
=

150) 2 3  2  3   2
151)  6  2  3  2

152) 3 5  2  3  
2

153)  2  5 154) 3 5  3  2  155)  7  1


2 2 2
7 2  6 2 
2 2 2
1 4 9 2 3 3 1 10 5
156)  x 2  x    157)  x 2  x    158)  x 2  x   
2 5 2 3 4 2 5 3 2
2 2 2
4 1 9 8 1 3 6 10 1
159)  x 2  x    160)  x 2  x    161)  x 2  x   
3 2 2 3 4 2 5 3 4

Răspuns: 129) x4 + 4x3 + 10x2 + 12x + 9; 130) 4x4 – 4x3 – 3x2 + 2x + 1; 131) x4 – 6x3 +
7x2+ 6x + 1; 132) 9x4 – 12x3 – 20x2 + 16x + 16; 133) x4 – 2x3 – 9x2 + 10x + 25; 134) x4
+ 4x3 +12x2 + 16x + 16; 135) 9x4 – 6x3 – 23x2 + 8x + 16; 136) 16x4 + 24x3 – 7x2 – 12x
+ 4; 137) 4x4 – 20x3 + 29x2 – 10x + 1; 138) 25x4 – 10x3 + 41x2 – 8x + 16; 139) x4 + 6x3
+ 5x2 – 12x +4; 140) 4x4 – 4x3 + 21x2 – 10x + 25; 141) 9x4 – 18x3 + 3x2 + 6x + 1;
142) 36x4 – 24x3 – 32x2 + 12x + 9; 143) 16x4 – 40x3 + 41x2 – 20x + 4; 144) 0,25x4 +
1,2x3 + 3,84x2 + 5,76x +5,76; 145) 2,56x4 + 4,8x3 + 10,57x2 + 7,8x + 6,76; 146)
11,56x4 – 17,68x3 + 16,96x2 –7,8x + 2,25;147) 19,36x4 – 14,08x3 – 19,44x2 + 8x + 6,25;
148) 7,84x4 – 17,92x3 + 29,84x2-22,4x + 12,25; 149) 40,96x4 – 20,48x3 – 55,04x2 +
14,4x + 20,25; 150) 23  4 6  12 3 
 6 2 ; 151) 11  4 3  6 2  2 6 ; 152) 56  6 10  18 5  6 2 ; 153) 40  4 14  10 7 ;
1 4 113 2
154) 52  6 15  12 5  4 3; 155) 35  4 42  2 6  4 7 ; 156) x 4  x 3  x  12 x 
4 3 18
81 4 41 2 9 9 1 4 4 3 109 2 50 25 16 4
 ; 157) x 4  x 3  x  x  ; 158) x  x  x  x ; 159) x 
4 9 16 4 4 25 3 9 3 4 9
4 49 2 9 81 64 4 4 3 129 2 3 9 36 4 527 2
 x3  x  x  ; 160) x  x  x  x  ; 161) x  8x 3  x 
3 4 2 4 9 3 16 4 4 25 45
5 1
 x .
3 16

162) (x – 2)2 + (x – 3)·(x + 3) = 163) (x + 4)2 – (2x – 5)·(2x + 5) =


164) (2x – 3)2 – (x – 5)·(x + 5) = 165) (3x – 6)·(3x + 6) – (4x +1)2 =
166) (2x – 3)·(2x + 3) – (3x – 1)2 = 167) (x + 8)·(x – 8) – (5x + 3)2 =
168) (3x – 4)2 – (2x – 3)·(2x + 3) – 5·(x2 – x + 2) =
169) (2x2 – x – 2)2 – (x + 3)2 – 3·(x – 2)·(x + 2) =
170) 2·(x2 + 2x + 3)2 – (x – 4)·(x + 4) – (x – 1)2 =
171) (x2 + x – 3)2 – (2x + 5)·(2x – 5) – (3x + 1)2 =
172) (4x2 – 5x + 1)2 – (6x – 1)·(6x + 1) – (1 – 4x)2 =
173)  2 x  1  2   x  2    x  2  
2

174)  x  3    x  5    x  5   3   2 x  1 
2

175) 3   x  2    2 x  1   x  2    x  2  
2 2

176) 2   x  5    3 x  1   3 x  1  4   5 x  1 
2

177)  x 5  3   x 5  3  3 2 x  2 3  
2

178)  x 3  2    x 2  3    x  5    x  5  
2 2

179)  4 x 2  3    2 x 6  3  x   4 6  1 
2 2

180)  x  3    3  x   2   x  7    x  7   181)  x      
2 2 2 2 2
3 2 3x 2x 
2 2
1 2 1 1 1 1 4 1 4 2 4 2
182)  x     x     x    183)  x     x     x   
2 3 2 3  2 3 5 3 3 3 3 3
2 2
2 3 3 1 3 1 7 2 3 2 3 2
184)  x     x     x    185)  x     x     x   
 7 4   5 2   5 2  3 5   4 5   4 5 
2 2
1 1 6 3  6 3 1 3 6 3 6 3
186)  x     x     x    187)  x     x     x   
6 2 5 5  5 5 4 5 7 4 7 4

Răspuns: 162) 2x2 – 4x – 5; 163) – 3x2 + 8x + 41; 164) 3x2 – 12x + 34; 165) – 7x2 – 8x
– 37; 166)– 5x2 + 6x – 10; 167) – 24x2 – 30x – 73; 168) – 19x + 15; 169) 4x4 – 4x3 –
11x2 – 2x + 7; 170) 2x4 + 8x3 + 18x2 + 26x + 33; 171) x4 + 2x3 – 18x2 – 12x + 33;
172)16x4 – 40x3 – 19x2 – 2x + 1;
173) 2 2 x  5;174) 8  3; 175) 4 x 2  9; 176)  x 2  7; 177) 23x 2  12 x 6  3; 178) 4; 179) 8 x 2  x;
2 5 256 2 8 5 341 2 3 13
180) 20; 181)  x 2  2 6 ; 182)  x  ; 183)  x  x  ; 184)  x  x ; 185)
3 9 225 15 9 1225 7 16
703 2 28 8 1271 2 1 61 527 2 3 369
x  x ; 186)  x  x ; 187)  x  x .
144 15 25 900 6 100 784 10 400

188) (2,4x – 1,5)2 – (3,3x – 1,2)·(3,3x + 1,2) + 9x·(0,57x + 0,8) =


189) (7,2x – 3,5)2 – (2,4x – 1,9)·(2,4x + 1,9) – 6x·(7,68x – 8,4) =
190) (8,5x – 3,2)2 – (4,9x – 5,7)·(4,9x + 5,7) – 4x·(12,06x – 13,6) =
191) (9,3x + 6,1)2 – (6,4x – 8,9)·(6,4x + 8,9) – 2x·(22,765x + 56,73) =
192) (7,6x – 3,3)2 – (3,8x – 5,6)·(3,8x + 5,6) –6x·(7,22x – 8,36) =
193) (8,4x – 5,7)2 – (2,8x – 5,4)·(2,8x + 5,4) – 4x·(15,68x – 23,94) =

Răspuns: 188) 3,69; 189) 15,86; 190) 42,73; 191) 116,42; 192) 42,25; 193) 61,65;